Addressing Educational Inequities in Urban Slums: A Narrative Review - Bhattrai , Namrata (International Research Journal of MMC, 2024)
This study examines the challenges faced by children living in urban slums regarding access to education, drawing insights from a systematic process 27 published journal articles, academic papers and Seminar reports are selected Among these, 16 were chosen for detailed discussion, resulting key findings on socio-economic barriers, parental education levels, and awareness gaps hampering educational opportunities for slum-dwelling children. Findings prevalent problems as inadequate infrastructure, ineffective teaching methods, and parental disengagement exacerbating educational disparities. Study highlights interventions including skill development programs, targeted public initiatives, and policy reforms to address these challenges. Recommendations emphasize collaborative efforts among stakeholders to implement educational policies, improve infrastructure in government schools, and enhance parental awareness. Adopting diverse social work approaches is recommended to address the multifaceted challenges confronting slum communities. Implementing these interventions can contribute to fostering more equitable and inclusive education system, thereby advancing the well-being of all children in urban slums.